2010
DOI: 10.1111/j.1559-1816.2010.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

Death Qualification as Systematic Exclusion of Jurors With Certain Religious and Other Characteristics

Abstract: The death‐qualification process has been criticized because it tends to eliminate certain groups of individuals at a higher rate than others. This study examined whether the process systematically excludes jurors based on religious characteristics, justice philosophy, cognitive processing, and demographics. Results indicated that death qualification can be predicted by religious affiliation, devotionalism, fundamentalism, and Biblical interpretism; but not evangelism. Death qualification is predicted by the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…According to the 2010–2016 General Social Survey data, the south central and south Atlantic regions have the highest proportion of fundamentalists, particularly the eastern south central region (50% identify as fundamentalists). Moreover, religious fundamentalists are more likely to be death qualified (Summers, Hayward, & Miller, ), and thus, a petit capital jury might be disproportionately composed of religious fundamentalists compared to the jury pool in many jurisdictions. Therefore, attorneys in these jurisdictions might be especially mindful of this research when trying death penalty cases before a jury.…”
Section: Discussionmentioning
confidence: 99%
“…According to the 2010–2016 General Social Survey data, the south central and south Atlantic regions have the highest proportion of fundamentalists, particularly the eastern south central region (50% identify as fundamentalists). Moreover, religious fundamentalists are more likely to be death qualified (Summers, Hayward, & Miller, ), and thus, a petit capital jury might be disproportionately composed of religious fundamentalists compared to the jury pool in many jurisdictions. Therefore, attorneys in these jurisdictions might be especially mindful of this research when trying death penalty cases before a jury.…”
Section: Discussionmentioning
confidence: 99%
“…Lindsey et al (2008) proposed ways in which lawyers can use religion to select a jury. Although some jurisdictions forbid such practices, it is still allowed in most of the United States (Miller & Bornstein, 2006; Miller & Hayward, 2008; Summers, Hayward, & Miller, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research conducted in several local jurisdictions in Florida found that, among other things, death-qualified jurors were more likely to endorse racist, sexist, and homophobic attitudes (Butler, 2007a), were more susceptible to potentially prejudicial pretrial publicity (Butler, 2007b), and more responsive to victim impact testimony (Butler, 2008). Researchers elsewhere also found that death qualification not only eliminated a disproportionate number of women and nonwhites but also members of certain religious groups, especially Catholics (Summers et al, 2010). Although many of these studies were conducted with local samples from individual jurisdictions that were not necessarily representative of jurors more broadly, the results underscored the fact that there was, if anything, more reason to focus on the biasing effects of death qualification than in the past.…”
Section: The Need For New Death Qualification Researchmentioning
confidence: 99%